2009
DOI: 10.1603/033.046.0117
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofBorrelia burgdorferiandBorrelia lonestariin Birds in Tennessee

Abstract: Lyme disease in the United States is caused by the bacterial spirochete Borrelia burgdorferi s.s. (Johnson, Schmid, Hyde, Steigerwalt, and Brenner), which is transmitted by tick vectors Ixodes scapularis (Say) and I. pacificus (Cooley and Kohls). Borrelia lonestari, transmitted by the tick Amblyomma americanum L., may be associated with a related syndrome, southern tick-associated rash illness (STARI). Borrelia lonestari sequences, reported primarily in the southeastern states, have also been detected in ticks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
0
27
0
4
Order By: Relevance
“…Borrelia burgdorferi was identified in only two ticks (one larva, one nymph). In North America, birds are competent reservoirs for this species (Jordan et al, 2009), whereas European strains of Bo. burgdorferi occur in bird-feeding ticks even less frequently than Bo.…”
Section: Discussionmentioning
confidence: 99%
“…Borrelia burgdorferi was identified in only two ticks (one larva, one nymph). In North America, birds are competent reservoirs for this species (Jordan et al, 2009), whereas European strains of Bo. burgdorferi occur in bird-feeding ticks even less frequently than Bo.…”
Section: Discussionmentioning
confidence: 99%
“…Shariat et al (2007) reported B. burgdorferi from 2 of 18 pooled samples of D. albipictus removed from white-tailed deer in Cheatham County. Similarly, Jordan et al (2009) reported the pathogen from 14% of wild turkey and 17% of migratory waterfowl blood samples collected from a site in middle Tennessee and reported further detections from these species in ten surrounding counties. A. americanum was the most common tick collected in that study; no I. scapularis was observed.…”
Section: Discussionmentioning
confidence: 87%
“…Several species of birds act as hosts for one or more stages of ticks and may spread ticks and pathogens to various parts of the world (Ogrzewalska et al 2008(Ogrzewalska et al , 2009a(Ogrzewalska et al , b, 2011Ioannou et al 2009;Jordan et al 2009). …”
Section: Introductionmentioning
confidence: 99%